Public and Private Higher Education Institutions in Malaysia: Competing, Complementary or Crossbreeds as Education Providers - Wan Chang Da (Kajian Malaysia, 2007)
Delivery of higher education used to be exclusive to the public sector in Malaysia. However, legislative changes made in 1996 led to the coexistence of public and private higher education institutions. In 2007, there were 20 public universities compared to more than 500 private institutions, of which 30 are currently categorised as universities or university colleges. Looking at their respective roles as higher education providers, public and private institutions display characteristics of being substitutes while at the same time serving complementary roles to one another. This dichotomy between public and private higher education institutions can, in fact, be seen as inclining towards a hybrid model that allows both to operate within a single system of higher education provision in the country. Such a hybrid model is evident in how the clientele is being divided between public and private higher institutions. It is also evident in the different roles played by the respective faculty members as well as in the programmes being made available in either type of institutions.